Effect of methadone and valproate combination on morphine withdrawal-induced anxiety and depression in male mice - Vahidi S; Khalili M; Kiasalari Z; Yaghoutpoor E (مجله دانشگاه علوم پزشکی گرگان, 2014)
Background and Objective: Anxiety and depression are experienced following addicted patients durg withdrawal. This study was done to determine the effect of methadone and valproate combination on morphine withdrawal-induced anxiety and depression in male mice. Methods: In this experimental study, ninety-eight male mice were allocated into acute and chronic categories. Animals in acute chronic categories allocated into seven groups including: saline, morphine, methadone (10 mg/kg/bw), valproate (150 mg/kg/bw), three groups of valproate+methadone, in of ratio 1:1, 2:1 and 1:2. Animals were received escalating dose of morphine for 8 consecutive days except saline group. In chronic group, drugs were injected for 30 minutes before morphine administration, while in acute group the drugs were used only at day 8. Anxiety and depression due to naloxone injection (5 mg/kg/bw) was investigated by elevated plus-maze, tail-suspension and open field tests. Results: In the chronic group, valproate + methadone (2:1) combination therapy showed a significant increase in the percentage of open arm entries (53.86±1.9) and percentage of time spent in the open arm (58.58±4.15) compared to the morphine group, with a percentage of entering (28.12±2.03) and percentage of time (17.88±1.77) (P<0.05). In open field test, the ratio of the number to the duration of time spent in the central square, in the combination therapy groups of methadone+valproate (27±2), valproate+methadone (1:2) and valproate+methadone (2:1) were significantly increased in compare to the morphine group (P<0.05). In tail-suspension test, duration of immobility as an indicator of depression, in the treatment group of valproate+methadone (2:1) was significantly reduced (P<0.05). Conclusion: Valproate and methadone combination therapy particularly in ratio of 2:1 can reduce morphine withdrawal-induced anxiety and depression in animal model.